Accounting issues of a sole proprietorship company in Kelantan: A case study of XYZ Hardware - Amir Hamzah Tamam (2015)
XYZ Hardware is a retail hardware store that focusing on selling high quality paints, housewares, electrical supplies, plumbing supplies, tools, gardening and cleaning supplies. The company was founded in 2001 in Tanah Merah, Kelantan and experienced steady growth during the year. The type of business is ‘sole-proprietorship’ and is owned by a local hailed from Tanah Merah, Kelantan. The study identified poor record-keeping as one of the contributing factors to negative audit results. Records management was still not being taken seriously in XYZ Hardware as in most cases it was not utilized to support field audit process. The recommendation made was that the company should improve its accounting system by implementing the strategies that had been lay down in order to avoid more mistakes in the future. The researcher also stress that as a good citizen, taxpayer must have positive attitude by following all the guidelines and regulations that had been set by the government.